Effects of milk fat, unhydrogenated and partially hydrogenated vegetable oils on serum lipoproteins in growing pigs - Jauhiainen, Matti; Aro, Antti; Blomqvist, Soile; Kemppinen, Asmo; Alaviuhkola, Timo; Antila, Pirkko (gb, 1993)
1. Crossbred Yorkshire (Yorkshire*Landrace) pigs were fed butter oil, cream, low erucic acid rapeseed oil, sunflower oil and partially hydrogenated sunflower oil in amounts representing 30% of energy for periods of up to 13 weeks. 2. After 13 wk of feeding serum total cholesterol levels of pigs fed milk fat were significantly higher than of pigs fed vegetable oils. 3. The difference in cholesterol was mainly due to an increase in the density range of 1.063-1.125 g/ml containing pig LDL2 and some HDL. 4. A shift towards smaller LDL paricle size was apparent in pigs fed milk fat. 5. The effects of dietary trans fatty acids did not differ from cis polyunsaturated or monounsaturated fatty acids.